CircRNA-regulated immune responses of asian honey bee workers to microsporidian infection - Zhu, Zhiwei; Wang, Jie; Fan, Xiaoxue; Long, Qi; Chen, Huazhi; Ye, Yaping; Zhang, Kaiyao; Ren, Zhongmin; Zhang, Yang; Niu, Qingsheng; Chen, Dafu; Guo, Rui (Frontiers in Genetics, 2022)
Nosema ceranae is a widespread fungal parasite for honey bees, causing bee nosemosis. Based on deep sequencing and bioinformatics, identification of circular RNAs (circRNAs) in Apis cerana workers’ midguts and circRNA-regulated immune response of host to N. ceranae invasion were conducted in this current work, followed by molecular verification of back-splicing sites and expression trends of circRNAs. Here, 10185 and 7405 circRNAs were identified in the midguts of workers at 7 days (AcT1) and 10 days (AcT2) post inoculation days post-inoculation with N. ceranae. PCR amplification result verified the back-splicing sites within three specific circRNAs (novel_circ_005123, novel_circ_007177, and novel_circ_015140) expressed in N. ceranae-inoculated midgut. In combination with transcriptome data from corresponding un-inoculated midguts (AcCK1 and AcCK2), 2266 circRNAs were found to be shared by the aforementioned four groups, whereas the numbers of specific ones were 2618, 1917, 5691, and 3723 respectively. Further, 83 52) differentially expressed circRNAs (DEcircRNAs) were identified in AcCK1 vs. AcT1 (AcCK2 vs. AcT2) comparison group. Source genes of DEcircRNAs in workers’ midgut at seven dpi were involved in two cellular immune-related pathways such as endocytosis and ubiquitin mediated proteolysis. Additionally, competing endogenous RNA (ceRNA) network analysis showed that 23 13) DEcircRNAs in AcCK1 vs. AcT1 (AcCK2 vs. AcT2) comparison group could target 18 14) miRNAs and further link to 1111 (1093) mRNAs. These target mRNAs were annotated to six cellular immunity pathways including endocytosis, lysosome, phagosome, ubiquitin mediated proteolysis, metabolism of xenobiotics by cytochrome P450, and insect hormone biosynthesis. Moreover, 284 164) internal ribosome entry site and 54 26) ORFs were identified from DEcircRNAs in AcCK1 vs. AcT1 (AcCK2 vs. AcT2) comparison group; additionally, ORFs in DEcircRNAs in midgut at seven dpi with N. ceranae were associated with several cellular immune pathways including endocytosis and ubiquitin-mediated proteolysis. Ultimately, RT-qPCR results showed that the expression trends of six DEcircRNAs were consistent with those in transcriptome data. These results demonstrated that N. ceranae altered the expression pattern of circRNAs in A. c. cerana workers’ midguts, and DEcircRNAs were likely to regulate host cellular and humoral immune response to microsporidian infection. Our findings lay a foundation for clarifying the mechanism underlying host immune response to N. ceranae infection and provide a new insight into interaction between Asian honey bee and microsporidian.